Teacher Education During the Covid-19 Pandemic: Tensions and Challenges of Initial Teacher Training Practices - Vanegas-Ortega, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The objective of the study is to characterize the ways of understanding and functioning of the formative triads of pedagogical practices, based on the decisions, tensions, and challenges faced by the initial teacher training programs in times of pandemic. The research used a qualitative-phenomenological perspective, inquiring into natural situations experienced by the formative triads of the pedagogical careers of 23 Chilean universities with recognized trajectories in teacher training. The interviews were conducted when the country was in a health emergency, that is, when schools and universities were carrying out remote teaching. The results show that the pandemic transformed the collaborative links between schools and universities, some links were broken, and others were strengthened, showing that the functioning of the triads is more declarative than real. In addition, the trainers (university tutor teacher and school guide teacher) faced two disconnected scenarios (school and university) that did not provide them with clear guidelines and concrete support for the development of their roles. This research has relevance for teacher training programs because it stresses the design of action plans to give continuity to practices in emergency situations and orients the evaluation of practice models to decide if they have the conditions to implement a model based on the formative triad. © 2024 by the authors.